Big Data Research in the Field of Endocrine Diseases Using the Korean National Health Information Database - Cho, Sun Wook; Kim, Jung Hee; Choi, Han Seok; Ahn, Hwa Young; Kim, Mee Kyoung; Rhee, Eun Jung (Endocrinology and metabolism (Seoul), 2023)
The Korean National Health Information Database (NHID) contains big data combining information obtained from the National Health Insurance Service and health examinations. Data are provided in the form of a cohort, and the NHID can be used to conduct longitudinal studies and research on rare diseases. Moreover, data on the cause and date of death are provided by Statistics Korea. Research and publications based on the NHID have increased explosively in the field of endocrine disorders. However, because the data were not collected for research purposes, studies using the NHID have limitations, particularly the need for the operational definition of diseases. In this review, we describe the characteristics of the Korean NHID, operational definitions of endocrine diseases used for research, and an overview of recent studies in endocrinology using the Korean NHID.